2021
DOI: 10.1007/s10113-020-01745-z
|View full text |Cite
|
Sign up to set email alerts
|

Possible changes in spatial distribution of walnut (Juglans regia L.) in Europe under warming climate

Abstract: Juglans regia L. is a species of great importance for environmental management due to attractive wood and nutritious fruits, but also high invasive potential. Thus, uncertainties connected with its range shift are essential for environmental management. We aimed to predict the future climatic optimum of J. regia in Europe under changing climate, to assess the most important climatic factors that determine its potential distribution, and to compare the results obtained among three different global circulation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 100 publications
1
12
1
1
Order By: Relevance
“…The pessimistic scenario (RCP8.5) assumes a CO 2 concentration of 1350 ppm and an average temperature increase of 2.6-4.8 °C by 2100this is a scenario of intensive economic growth with intensive use of fossil fuels (van Vuuren et al 2011;Harris et al 2014;IPCC 2014). To account for uncertainty across different global circulation models (GCMs) used in predicting future values of bioclimatic variables (Thuiller et al 2019;Paź-Dyderska et al 2021) , we used three GCMs and averaged the output to provide a more robust forecasts of range shifts. The three GCMs were -HadGEM2-ES , IPSL-CM5A-LR (Dufresne et al 2013), and MPI-SM-LR (Giorgetta et al 2013), reflecting, respectively, low, moderate, and high levels of change in climate conditions depending on scenarios of CO 2 concentration (Goberville et al 2015) .…”
Section: Potential Distribution Modelingmentioning
confidence: 99%
“…The pessimistic scenario (RCP8.5) assumes a CO 2 concentration of 1350 ppm and an average temperature increase of 2.6-4.8 °C by 2100this is a scenario of intensive economic growth with intensive use of fossil fuels (van Vuuren et al 2011;Harris et al 2014;IPCC 2014). To account for uncertainty across different global circulation models (GCMs) used in predicting future values of bioclimatic variables (Thuiller et al 2019;Paź-Dyderska et al 2021) , we used three GCMs and averaged the output to provide a more robust forecasts of range shifts. The three GCMs were -HadGEM2-ES , IPSL-CM5A-LR (Dufresne et al 2013), and MPI-SM-LR (Giorgetta et al 2013), reflecting, respectively, low, moderate, and high levels of change in climate conditions depending on scenarios of CO 2 concentration (Goberville et al 2015) .…”
Section: Potential Distribution Modelingmentioning
confidence: 99%
“…Besides genetic control, geographical and ecological conditions are important factors in determining the growth and fruit quality of walnut ( Diaz et al, 2005 ; Xu et al, 2016 ; Paź-Dyderska et al, 2021 ). It has been demonstrated that the interaction between genetic effects and environmental factors contribute to the heritability and thus the level of variation of many traits in walnut ( Sarikhani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The climate is the primary determinant of species distributions on a large spatial scale, affecting other interactions [122]. Another source of uncertainty in our model is the dependence on GCMs used in the study [110][111][112]. We decreased this uncertainty by averaging model predictions for four different GCMs.…”
Section: Discussionmentioning
confidence: 99%
“…We applied models to maps of current and future climatic scenarios to obtain predictions of G. materiarius distribution. For each SSP we averaged predicted species occurrence probability across the four GCMs, to reduce uncertainty connected with particular GCMs [110][111][112]. Then, maps with threshold values (true/false) were used to estimate the changes in the potential range, changing the values on maps with the future potential range from 1 to 2 [113].…”
Section: Modelling Species Distributionmentioning
confidence: 99%